A New Spherical Light Field Database for Immersive Telecommunication and Telepresence Applications - Zerman, Emin; Gond, Manu; Takhtardeshir, Soheib; Olsson, Roger; Sjöström, Mårten (Mid Sweden University, 2024)
This database is created by the Realistic 3D research group at Mid Sweden University, Sundsvall, Sweden. The database details are explained thoroughly in the publication which was published at the 16th International Conference on Quality of Multimedia Experience (QoMEX) in 2024. This database was also reviewed as part of the submission and publication process.

You can use this database in your work under the Creative Commons Attribution 4.0 International (CC-BY 4.0) licence, provided that you cite the database as below:

Zerman, E., Gond, M., Takhtardeshir, S., Olsson, R., & Sjöström, M. (2024). A Spherical Light Field Database for Immersive Telecommunication and Telepresence Applications. The 16th International Conference on Quality of Multimedia Experience (QoMEX). IEEE. DOI: 10.1109/QoMEX61742.2024.10598264

BibTeX:

@inproceedings{zerman2024spherical,  title        = {A Spherical Light Field Database for Immersive Telecommunication and Telepresence Applications},  author       = {Zerman, Emin and Gond, Manu and Takhtardeshir, Soheib and Olsson, Roger and Sj{\"o}str{\"o}m, M{\aa}rten},  booktitle    = {The 16th International Conference on Quality of Multimedia Experience (QoMEX)},  year         = {2024},  organization = {IEEE},  doi          = {10.1109/QoMEX61742.2024.10598264}}

This database contains 20 spherical light fields of 1 x 60 views, captured with a consumer-grade 360-degree camera: Insta360 X3. The capture was done using a dolly to ensure the separation between consecutive views is exactly 1 cm. In addition to the original captures, this database also provides outputs for two different use cases: compression and view synthesis. Several parameters, features, and objective quality metric values are also included.

N.B. Only the README file and this description have been updated after the initial submission on 2024-02-09.
Keywords: Signal processing; Machine learning; Telecommunications; omnidirectional; view synthesis; telepresence; light field compression; Telecommunications; Telekommunikation; Computer Sciences; Datavetenskap (datalogi)